Lung cancer screening in Finland: a prospective randomized trial - Viktor Wichmann; Sanna Iivanainen; Lauri Mattila; Veli-Pekka Kokkonen; Airi Jartti; Antti Kurtti; Riitta Kaarteenaho; Heidi Andersen; Antti Jekunen; Tuula Vasankari; Jussi Koivunen (Acta Oncologica)
Background: Early detection of lung cancer with low-dose computed tomography (LDCT) screening can shift diagnoses to early-stage disease and improve survival. However, LDCT has several challenges such as high false positive rate and indefinite cost-effectiveness. We report here secondary and exploratory endpoints of the Low-dose CT screening for lung cancer combined with different smoking cessation approach in Finland (LDCT-SC-FI) study including recruitment channels, LDCT performance, and long-term smoking cessation.